Analisis Kinerja Keuangan untuk Menilai Tingkat Kesehatan pada Koperasi Simpan Pinjam dan Pembiayaan BMT Projo Artha Sejahtera (PAS) di Bantul - Mujino Mujino; Ratih Kusumawardhani; Diah Cahyani (ITB AAS Indonesia Surakarta, 2021)
This study aims to investigate the health level of the savings and loan cooperatives and financing of BMT PAS in terms of: 1) Capital aspect; 2) Management aspect; 3) Liquidity aspect; 4) Aspect of compliance with syariah. This research is a type of quantitative descriptive research. The subject of this research is the savings and loan cooperatives and financing of BMT PAS in Bantul. The object of this research is the financial statements of 2015 to 2019. The data collection method were used documentation and questionnaire. The calculation use PAP technique was based on Deputy Regulation for the Supervision of the Ministry of Cooperatives and Small and medium Enterprises of Republic Indonesia Number 07/Per/Dep.6/IV/2016. The result of this research shows that health level of the savings and loan cooperatives and financing of BMT PAS 2015 to 2019 seen from; 1) Capital aspects of BMT PAS Bantul in 2015 to 2019 criteria are quite healthy; 2) Aspects management of BMT PAS Bantul in 2015 to 2019 criteria are quite healthy; 3) Aspects of liquidity of BMT PAS Bantul in 2015 to 2019 are healthy criteria; 4) Aspects of compliance with syariah principles BMT PAS Bantul from 2015 to 2019 healthy criteria. Keywords : Financial performance, health level, savings and loan cooperatives and syariah financing.